THE EFFECT OF WRITE “D” TECHNIQUE TO STUDENT’S WRITING SKILL IN COVID-19 ERA - Rini Yudiati; Ach. Andiriyanto; Anni Annisa (Journal of Innovation Research and Knowledge, 2023)
This study is aimed purposes to measuring whether There is a significant effect of Write “D” technique to the students’ writing skill. The writing achievement students of the third semester in healthy department are relatively low. Interview with the students indicates that writing is the most difficult subject of the four basic language skills of listening, speaking, reading, and writing. In this research, the writer use experimental research method by random sampling of the student class are determined as experiment groups (X) and control group (Y). In the experimental group was given special treatment in the learning process is carried out byWrite “D” Technique, while the comparison group will give conventional, where the students would be give a pretest before starting the treatment healthy department of wiraraja university of Sumenep. At the end of treatment, the writer gave the students a test, which is called posttest. To Achieve the four purpose of the study, the data will be analyzed by T-test analyses with the help of SPSS.20. The result turned out to confirm that there is effect on the Writing “D” to the student Writing skill. The result of the computation show. Write “D” mean value is 16,6 higher or better than Control Group (Conventional) that have mean value 15,96.